Cómo optimizar la seguridad en el uso de medicamentos en Urgencia - Herrada H, Luis; Jirón A., Marcela; Yáñez R., Nicolás (Revista Hospital Clínico Universidad de Chile, 2014)
Medication errors are defined as any preventable event that may cause harm to the patient or lead to inappropriate medication use. There are factors that determine the occurrence of medication errors in health services, such as: insufficient knowledge of patient care load, fast speed in care, variety and complexity of the routes of drug administration, among others. There are multiple studies in Emergency Departments where increased incidence of medication errors where observed. In our Emergency Department the frequency of medication errors was established at 29.4%. To avoid these errors, prevention strategies were generated depending on the type of error. As specific strategies in our emergency department we have assured the presence of a clinical pharmacist in the health team, local protocols for indications have been created and ongoing training of health personnel has been mandatory. The objective of these measures is to ensure quality and safety of patient care. We recognize that errors will occur due to the type of care we provide, and therefore we should implement measures at hand to reduce them.